2015
DOI: 10.1080/00343404.2014.965136
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Provision and Knowledge-Intensive Firms: A Causal Relationship?

Abstract: Despite the discussions about the importance of the digital economy, we are still far from understanding how Information and Communication Technologies (ICTs) affect economic activity in space. Recent studies have started untangling the spatial economic impact of ICTs, highlighting the potential use of ICTs as a local development tool. This paper contributes to this domain by exploring whether broadband Internet provision can act as an attractor for knowledge intensive business services in the US. Using Grange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…In this regard, Tranos and Gillespie () draw attention to how information is distributed among settlements through ‘digital highways' and that being part of such networks creates locational advantages. This view is supported by Tranos and Mack () who observe a positive impact of early adoption of digital technologies on the presence of knowledge‐intensive businesses in US counties. Similarly, while expressing concerns about a simultaneous relationship, Kolko () argues that broadband expansion could attract economic activity.…”
Section: Theoretical Backgroundmentioning
confidence: 78%
See 1 more Smart Citation
“…In this regard, Tranos and Gillespie () draw attention to how information is distributed among settlements through ‘digital highways' and that being part of such networks creates locational advantages. This view is supported by Tranos and Mack () who observe a positive impact of early adoption of digital technologies on the presence of knowledge‐intensive businesses in US counties. Similarly, while expressing concerns about a simultaneous relationship, Kolko () argues that broadband expansion could attract economic activity.…”
Section: Theoretical Backgroundmentioning
confidence: 78%
“…Industrial characteristics (such as high IT reliance) and firm size are also found to affect the relationship between telecommunications and regional development (Mack and Grubesic ; Kolko ). Moreover, the relationship between firm location and communication infrastructure may be complex and spatially heterogeneous as shown by Mack () and Tranos and Mack () in their studies on US counties.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some more recent literature have explored the effects on local business and entrepreneurship development. For instance, scholars are increasingly focusing on the effects of high-speed broadband on issues of regional development (Grubesic and Mack, 2015), on business innovation and entrepreneurship development (Alam and Adeyinka, 2016;Tranos and Mack, 2016) and on knowledge-intensive firms' differential performances (Mack and Rey, 2014) or firm-level productivity (Haller et al, 2015).…”
Section: Research Evidencementioning
confidence: 99%
“…A Wald test is then performed to indicate the preferred specification, which illustrates whether the lagged values of x improves the prediction of y or not. While the former result indicates that x Granger-causes y, the latter would signify the opposite (Hurlin and Venet 2001;Tranos 2012;Tranos and Mack 2016). In essence, Granger causality tests comprehend causality as temporal precedence between y and x.…”
Section: Methodological Approachmentioning
confidence: 99%